Risk Stratification for Detection of Coronary Artery Disease and Effectiveness of Sensitization Programme on Reduction of Risk for Coronary Artery Disease among Adults in Selected Urban Areas of Vijayapur (Indian Journal of Public Health Research & Development, 2022)
Background: Cardiovascular diseases, especially coronary heart disease (CHD), are epidemic in India. The Registrar General of India reported that CHD led to 17% of total deaths and 26% of adult deaths in 2001-2003, which increased to 23% of total and 32% of adult deaths in 2010-2013. In India, studies have reported increasing CHD prevalence over the last 60 years, from 1% to 9%-10% in urban populations and
Keywords: Risk Stratification, Coronary Artery Disease, Sensitization Programme, Adults